Immunization with a Synthetic Helicobacter pylori Peptide Induces Secretory IgA Antibodies and Protects Mice against Infection - David Espinosa-Ramos; Diana Caballero-Hernández; Ricardo Gomez-Flores; Armando Trejo-Chávez; Luis Jerónimo Pérez-Limón; Myriam Angélica de la Garza-Ramos; Reyes Tamez-Guerra; Patricia Tamez-Guerra; Cristina Rodriguez-Padilla (Canadian Journal of Infectious Diseases and Medical Microbiology)
Helicobacter pylori is a spiral Gram-negative bacterium associated with inflammation of the gastric mucosa, peptic ulcer, and gastric adenocarcinoma, whose treatment has failed due to antibiotic resistance and side effects. Furthermore, because there are no vaccines effective against H. pylori, an appropriate vaccine design targeting conserved/essential genes must be identified. In the present study, a H. pylori 50–52 kDa immunogen-derived peptide antigen with the sequence Met-Val-Thr-Leu-Ile-Asn-Asn-Glu (MVTLINNE) was used to immunize against H. pylori infection. For this, mice received an intraperitoneal injection of 100 μg of H. pylori peptide on the first week, followed by two weekly subcutaneous reinforcements and further 109 bacteria administration in the drinking water for 3 weeks. Thymic cells proliferative responses to concanavalin A, serum levels of IL-2, IL-4, IL-6, IL-10, IL-17, IFN-γ, and TNF-α cytokines, and IgG1, IgG2a, IgG2b, IgG3 IgM, and IgA immunoglobulins were evaluated. Significant (p<0.05) increases on lymphoproliferation and spleen weights after immunization were observed. In contrast, infection significantly (p<0.05) decreased lymphoproliferation, which was recovered in immunized mice. In addition, levels of serum TH1 and TH2 cytokines were not altered after immunization, except for the significant increase in IL-6 production in immunized and/or infected animals. Moreover, immunization correlated with plasma secretory IgA and IgG, whereas infection alone only elicited IgM antibodies. Peptide immunization protected 100% of mice against virulent H. pylori. MVTLINNE peptide deserves further research as an approach to the prophylaxis of H. pylori infection.